P189. Sarcoid neuropathy: Correlation of nerve ultrasound, electrophysiological and clinical findings. Issue 8 (August 2015) - Kerasnoudis, A.; Pitarokoili, K.; Woitalla, D.; Gold, R.; Yoon, M.-S.
<x xml:space="preserve">Abstract</x> Introduction We present the nerve ultrasound findings in sarcoid neuropathy and examine their correlation with electrophysiology and functional disability. Methods 40 healthy controls and 13 patients with sarcoid neuropathy underwent clinical, sonographic and electrophysiological evaluation a mean of 2.1 years (SD ± 0.7) after disease onset. Results Nerve ultrasound revealed significantly higher cross sectional area (CSA) values of the ulnar (elbow, p < 0.001), fibular (fibular head, p < 0.001), sural (between the gastrocnemic muscle, p < 0.001) and tibial nerve (ankle and popliteal fossa, p < 0.001), when compared to controls. The electroneurography documented significantly lower values of the (1) compound muscle action potentials (cMAP) in the median, fibular and tibial nerves (p < 0.001), (2) sensory nerve action potential (sNAP) in the median, ulnar and sural nerves (p < 0.001). A significant correlation between sonographic and electrophysiological findings in the group with sarcoid neuropathy, was found only between cMAP and CSA of the ulnar nerve at the elbow (r = 0.894, p < 0.001). Neither nerve sonography nor electrophysiology correlated with functional disability. Conclusions Sarcoid neuropathy seems to show predominantly CSA enlargement in peripheral nerves of the lower extremities, without any significant correlation to electrophysiological findings. The electroneurography documented signs of sensorimotor axonal loss in various peripheral nerves. Neither nerve sonography nor electrophysiology correlated with functional disability.